Communication Skills of Counselors in Bugis Culture: An Analysis of To-Riolo’s Thought using Gadamerian Hermeneutics - Hikmah, Muh. Syawal; Kaffah, Muhammad Silmi; Agussalim, Agussalim; Salam, Agung Surya; Mirdan, Moh. (IKIP Siliwangi, 2025)
This study aims to explore and uncover the meaning of integrating To-Riolo's philosophical thought into counselor communication skills grounded in Bugis cultural values. Employing a qualitative research design, the study uses the Gadamerian hermeneutic method, which emphasizes the analysis of the part and whole to understand and interpret the text deeply. The findings reveal several key communication skills embedded in To-Riolo's teachings: orderly communication (mattarêtte'), communication-based on ade,' rapang, and enrênnge madecennge gau (traditional norms and ethical considerations), and empathic listening as expressed through concepts such as iisênngi riolo'paunna (understanding the words of predecessors), naisseng to rapannge (understanding the interlocutor), ênrênnge adê’e (weighing norms), kuae wari'e (considering timing and context), and naenngêrranngi madecennge paunna' patujue ênrênnge gau' patujue (attentively listening to words and actions that are appropriate). This study implies that these culturally rooted communication skills can be developed into a culturally sensitive model for counselor communication within the Bugis community.